Different Lower-Limb Setup Positions Do Not Consistently Change Backstroke Start Time to 10 m - Gordon E. Barkwell; James P. Dickey (MDPI AG, 2020)
Backstroke starts involve the athlete starting from a flexed position with their feet against the pool wall and then extending their ankles, knees, hips and back to push off; however, swimmers can start in different positions. The purpose of this study was to evaluate the performance impact of different knee extension angles in the setup position for a backstroke start. Ten backstroke swimmers completed maximum-effort starts in each of two setup positions: one with the knees maximally flexed, and one with the knees less flexed. The start handles and touchpad were instrumented with multi-axial force sensors. Activity of major hip and knee extensors was measured using surface electromyography. Body position in the sagittal plane was recorded using high-speed cameras. There was no overall difference in time to 10 m between the two conditions (p = 0.36, dz = 0.12), but some participants showed differences as large as 0.12 s in time to 10 m between start conditions. We observed that starts performed from a setup position with less knee flexion had an average 0.07 m greater head entry distance (p = 0.07, dz = 0.53), while starts from a setup position with maximal knee flexion had an average 0.2 m/s greater takeoff velocity (p = 0.02, dz = 0.78). Both head entry distance and takeoff velocity are related to start performance, suggesting each position may optimize different aspects of the backstroke start. Coaches should assess athletes individually to determine which position is optimal.